Diseño de una antena con tecnología de Superficies Inteligentes Reflectantes (RIS) para redes inalámbricas en la banda de 2.4 GHz - Muso Maisanche, Jenniffer Maite (2024)
The present research aims to design an antenna with reflective smart surface (RIS) technology, working in the S-band frequency, specifically at the frequency of 2.4 GHz and, therefore, can be used in wireless communications. The RIS antenna design consists of a patch antenna on the front side, the slotted plane on the central part, and the ground plane on the back. In the central part, the RIS consists of positive intrinsic negative diodes (PIN), which, according to their configuration, will allow to obtain an offset of 0°, 90° and 180° between the proposed configurations. The behavior of the RIS antenna in its unit cell was analyzed using the periodic boundary conditions method and the Floquet port through the electromagnetic software CST Studio Suite, exciting the reflection mode (Zmax) to observe the behavior of the unit cell before an incident wave. A pyramidal horn antenna was used to feed the array consisting of N numbers of reflecting elements; the latter was designed to operate at a center frequency of 2.4 GHz. In order to analyze the performance of the RIS antenna, its behavior at both 2.4 GHz and 5 GHz is compared. After performing the relevant simulations and evaluating the results, it was observed that the proposed antenna model presented satisfactory values in its gain, directivity and bandwidth parameters for the two frequencies, this on an array of 64 elements of unitary waves, that is a RIS antenna of 8 x 8 reflecting elements.